Pendapat Syafi’iyah Dan Hanafiyah Tentang Wali Adhal Karena Calon Suami Berjarak Jauh Ditinjau Dari Maslahah Mursalah - Ahmad Khotim (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2021)
Background. Marriage is a very strong contract (mitsaqan galidzan) between a man and a woman as a form of worship to Allah SWT to form a family that is sakinah mawadah wa rohmah. Marriage in the Indonesian legal system, especially for those who embrace Islam, requires a marriage guardian which is regulated in articles 19 to 23 of the Compilation of Islamic Law (KHI) and article 18 of the minister of religion regulation number 11 of 2007 concerning registration of marriages. Guardianship is an inseparable part of a marriage, because a guardian is a person who must be present when a marriage takes place. The involvement of a guardian in a marriage determines (valid or not) the marriage contract in the view of Islamic law.Aim. This research was written to answer the questions outlined in 2 (two) problem formulations, namely: (1) How to find out the opinion of Imam Shafi'i and Imam Hanafi regarding the law of guardianship because the reason is that the prospective husband is far away. (2) What is the legal adhalnya guardian because the prospective husband is far away in the view of Maslahah Mursalah.Methods. The library data needed in this study will be collected using collection techniques. in this qualitative research will use inductive analysis.Results. According to Syafi'iiyah the existence of a marriage guardian absolutely must exist in a marriage. Because marriage without a guardian's permission is invalid. Meanwhile, Hanafiyah's permission for a guardian is not a legal requirement for marriage, but only complements the marriage vows. Based on Maslahah Mursalah's analysis regarding the adhal of a guardian for the reason that the husband-to-be comes from a remote area, there is no argument from the Koran or hadith that prohibits it. There are also no prohibitions (obstacles) on marriage in the form of kinship relations, sexual relations, and sexual relations (rodlo') to be carried out by the bride and groom.